Financial Inclusion Across Gender among University Students after the Implementation of the 3-Tier KYC Requirement Policy in Nigeria - Mogbolu, Favoured; Igbinedion, Sunday (Acta Universitatis Danubius. Œconomica, 2023)
This study examines financial gender differences among university students, theoretically, categorized as persons with small scale financial needs. Policy reports and academic research conclude that persistence of the financial gender gap, a major factor in financial exclusion over time in developing economies, is linked to regulatory barriers, and levels of education and financial literacy. The study seeks to ascertain the extent to which removal of regulatory barriers to account ownership for small scale users of financial services, achieved by the implementation of the financial inclusion supply side, the 3-Tier KYC requirement Policy by Nigerian banks, reduced financial gender gap in an environment of tertiary education status. Data used for the study is from survey questionnaires, and data analyses involved tables of frequencies and percentages and the chi-square test. The findings indicate no gender difference in both ownership of accounts with formal financial institutions, usage of financial providers and of other financial services including, receipts of funds, payments and borrowings. The study concludes that formal financial gender differences do not exist for the group. The findings imply that 100% financial inclusion is attainable. Policy makers and practitioners can achieve this by use of regulatory policies that remove barriers to the provision of formal financial services for persons with small scale financial service needs, coupled with strong financial literacy campaigns.